Sensory and physicochemical attributes of chocolate soft candy with different gelling agents. - Rahman, Taufik; Putri, Siti Khudaifanny Dasa Febrianti Asna (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Indonesia is one of the cocoa-producing countries. One of the modifications of processed cocoa is chocolate soft candy. This study aimed to determine the effect of the type of gelling agent on the sensory and physicochemical characteristics of chocolate soft candy. This study used a completely randomized design with one factor using several gelling agents, namely gelatin, carrageenan, and konjac, with the control being soft candy without adding the gelling agent. The analyses included texture, moisture content, ash content, reducing sugar levels, and sensory evaluation. The results showed that adding several types of gelling agents significantly affected the soft candy produced. The highest moisture content of soft candy was the treatment with 12.26% gelatin. The minor ash content added gelatin of 0.71%, and the highest reducing sugar levels added carrageenan of 10.21%. The highest value of taste and texture parameters is obtained by adding konjac soft candy.